Pengaruh Suhu dan Waktu Pengeringan terhadap Karakteristik Teh Herbal Daun Mimba (Azadirachta indica A. Juss) - Alfira, Kanza; Yusasrini, Ni Luh Ari; Diah Puspawati, I Gusti Ayu Kadek (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 2 (2023): Jurnal ITEPA, 2023)
This study aimed to determine the effect of drying temperature and time on the characteristics of neem leaf herbal tea and to obtain the right drying temperature and time to produce neem leaf herbal tea with the best characteristics. The experimental design used was a factorial completely randomized design (CRD) with two factors. The first treatment namely drying temperatures (50°C, 60°C, 70°C) and the second treatment namely drying time (3, 4, 5 hours). The results showed that the interaction of drying temperature and time in neem leaf herbal tea had a significant effect (P<0,05) on moisture content, ash content, extract content in water, total flavonoid content, total phenolic concent, antioxidant activity, and taste. The best treatment was drying neem leaf herbal tea at 70°C for 5 hours with the characteristics: water content 3.41%; ash content 5.93%; extract content in water 38.82%; total flavonoid content 3.79 mg QE/g; total phenolic content 6.54 mg GAE/g; antioxidant activity 62.45% and based on the IC50 of 706.65 ppm; neutral color, aroma were slight liked, taste were bitter and neutral, overall acceptance were neutral.